Divergent receiver responses to components of multimodal signals in two foot-flagging frog species. - Doris Preininger; Markus Boeckle; Marc Sztatecsny; Walter Hödl (PLoS ONE)
Multimodal communication of acoustic and visual signals serves a vital role in the mating system of anuran amphibians. To understand signal evolution and function in multimodal signal design it is critical to test receiver responses to unimodal signal components versus multimodal composite signals. We investigated two anuran species displaying a conspicuous foot-flagging behavior in addition to or in combination with advertisement calls while announcing their signaling sites to conspecifics. To investigate the conspicuousness of the foot-flagging signals, we measured and compared spectral reflectance of foot webbings of Micrixalus saxicola and Staurois parvus using a spectrophotometer. We performed behavioral field experiments using a model frog including an extendable leg combined with acoustic playbacks to test receiver responses to acoustic, visual and combined audio-visual stimuli. Our results indicated that the foot webbings of S. parvus achieved a 13 times higher contrast against their visual background than feet of M. saxicola. The main response to all experimental stimuli in S. parvus was foot flagging, whereas M. saxicola responded primarily with calls but never foot flagged. Together these across-species differences suggest that in S. parvus foot-flagging behavior is applied as a salient and frequently used communicative signal during agonistic behavior, whereas we propose it constitutes an evolutionary nascent state in ritualization of the current fighting behavior in M. saxicola.